2019
DOI: 10.9778/cmajo.20180191
|View full text |Cite
|
Sign up to set email alerts
|

Impact of school vaccination mandates on pediatric vaccination coverage: a systematic review

Abstract: Competing interests: Devon Greyson reports grants from the British Columbia Immunization Committee during the conduct of the study. No other competing interests were declared. This article has been peer reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 43 publications
1
21
0
Order By: Relevance
“…Using NIS datasets 2008-2017, we found that children and adolescents residing in states with S or C + S requirements were more likely to initiate and complete Hep A vaccination, compared with those residing in states without such requirements. Our findings are similar to other studies that have evaluated the impact of other school vaccination requirements on vaccination rates [ 8 ].…”
Section: Discussionsupporting
confidence: 91%
“…Using NIS datasets 2008-2017, we found that children and adolescents residing in states with S or C + S requirements were more likely to initiate and complete Hep A vaccination, compared with those residing in states without such requirements. Our findings are similar to other studies that have evaluated the impact of other school vaccination requirements on vaccination rates [ 8 ].…”
Section: Discussionsupporting
confidence: 91%
“…These mandates may have already positively impacted vaccine acceptance [29]. While there is strong evidence supporting the net benefit of mandates for previous vaccines among school children [30] and healthcare facilities [31], the US does not have experience implementing vaccine mandates in situations where about a quarter of the population does not want the vaccine even after widespread free access. The highly politicized and polarized COVID-19 environment in the US may increase the risk of pushback to mandates.…”
Section: Discussionmentioning
confidence: 99%
“…As an evidence-based strategy, school-entry requirements have proved to increase vaccination rates among children and youth [ 4 ]. The Advisory Committee on Immunization Practices (ACIP) recommends the HPV vaccine as a routine vaccine for girls (since 2006) and boys (since 2011) at ages 11–12 years old [ 5 ].…”
Section: Introductionmentioning
confidence: 99%